Relationship between Diabetic Retinopathy, and Diabetic Nephropathy - Debnath, Purabi Rani; Debnath, Dilip kumar; Bhowmik, Narayan Chandra (Bangladesh Medical Journal, 2019)
Diabetic nephropathy is accountable for nearly third of the world cases of last step of renal disease; it becomes a major public health problem with social and economic burden. To assess the relationship between Diabetic Retinopathy and Diabetic Nephropathy in Type II Diabetes Mellitus patients. The present study was a cross sectional study conducted in the department of Ophthalmology at BIRDEM General Hospital, Dhaka, over a period of 12 months during March 2018- February’ 2019 and were assess for the relationship between Retinopathy and Nephropathy. All patients of Type II Diabetes Mellitus patients with Diabetic Retinopathy and Diabetic Nephropathy were included in the study. Majority (64.0%) patients had diabetic nephropathy and 36(36.0%) had not diabetic nephropathy. Almost three fourth (73.4%) patients was found diabetic retinopathy in diabetic retinopathy and 27(54.0%) in without diabetic retinopathy. The difference was statistically significant (p<0.05) between two group. This study suggests that Diabetic Nephropathy has a significant association with the presence of Diabetic Retinopathy in persons with Type II DM. Bangladesh Med J. 2019 May; 48 (2): 24-27